ANALISIS PENGARUH ETOS KERJA DAN LINGKUNGAN KERJA TERHADAP MOTIVASI DAN KINERJA PEGAWAI - Fransisca Lamere (UPAJIWA, 2020)
This research aims to determne the effect of Work Ethic and Work Environment on Employee Performance at the Regional Development Planning Agency of the Tanimbar Islands Regency with Motivation as an Intervening Variable. Participans from this research were taken from employees of BAPPEDA Kabupaten Kepulauan Tanimbar. The method of data collection in this research was conducted by using a questionnaire (questionnaire). The technique of data analysis applied in this research is Partial Least Square (PLS) with SmartPLS 3.2.7 software. The results in this research are Work Ethics that have a significant effect on motivation but have no significant effect on employee performance, Work Environment has a significant effect on motivation but not significantly on employee performance, motivation does not have a significant effect on performance, Worck Ethic does not significantly influence performance through motivation. Work Environment does not have a significant effect on performance through motivation. Key Words: Work Ethic, Work Environment, Employee Performance, Motivation